Almanack da Parnahyba: desejo de modernidade sob o véu da barbárie em Parnaíba - Piauí (1924 - 1941) - Sousa, Cleto Sandys Nasciemento (2018)
This thesis is part of the Almanack of Parnaíba, produced and edited by Benedicto dos Santos Lima, in the city of Parnaíba, from 1924 until 1941, and in its articulation with the advent of modernity in the country. We seek to highlight and discuss the historically situated discursive plots, the fruits of a view on sociocultural experiments and, at the same time, as social instituting dimensions, especially considering the sensibilities and modern worldviews. Through texts, photographs and advertisements that acted in the formation of a local imaginary about the lived experiences, Parnaíba reveals itself, in the pages of Almanack, a modern city forged by images planned by the publishers’ interests. In this sense, the general objective of the research is to analyze how the Parnaíba Almanac "sold" the city of Parnaíba under the bias of European modernity, divulged its ideals, exalted its society and consecrated its wealthiest inhabitants from 1924 until 1941. In order to analyze the Almanacks, the theoretical framework establishes a dialogue between authors as Le Goff (1994), Chartier (1999), Certeau (1994), Aragão (2014), Ferreira (2001) and Dutra (2005), and documentary and hemerographic sources. To discuss the city of Parnaíba, the dialogue was established with local authors such as Mendes (1994), Lima (2008) and Nascimento (2001). The methodology used is anchored in the assumptions of historical research and based on primary and secondary sources. The Almanack is a privileged source to understand the modern historical formation of sensibilities and social practices, as a window that opens to very distant and at the same time very close cultural universes.